Bayard Rustin : behind the scenes of the civil rights movement - Haskins, James, 1941- (Hyperion Books for Children, 1997)
A biography of Bayard Rustin, a skillful organizer behind the scenes of the American civil rights movement whose ideas stongly influenced Martin Luther King, Jr.